Investigations into the specific throughput stability of conical feed zones over the rotation speed during the direct processing of polypropylene regrind - Rempel, Timm; Brüning, Florian (ANTEC)

Devulcanization behavior of SBR-based GTR compounds - Petzke, Jonas Dirk Rudolf Helmut

Differences of producing head fakes with and without a social partner - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (67th Conference of Experimental Psychologists)
Keywords: deception; action preparation; perception; movement planning; sport psychology

High-Speed Mach-Zehnder Modulator with Linear Segmented On-Chip Drivers in Photonic 45nm SOI-CMOS Technology - Kress, Christian; Schwabe, Tobias; Mihaylov, Martin Miroslavov; Scheytt, J. Christoph
We present an electronic-photonic co-designed Mach-Zehnder modulator with linear segment drivers in a photonic SOI-CMOS technology with an EO 3-dB bandwidth of ≥ 27 GHz and data transmission up to 64 Gbit/s without pre-emphasis.

Quantum resonances and scattering poles of classical rank one locally symmetric spaces - Delarue, Benjamin; Hilgert, Joachim (Journal of Lie Theory)
For negatively curved symmetric spaces it is known that the poles of the scattering matrices defined via the standard intertwining operators for the spherical principal representations of the isometry group are either given as poles of the intertwining operators or as quantum resonances, i.e. poles of the meromorphically continued resolvents of the Laplace-Beltrami operator. We extend this result to classical locally symmetric spaces of negative curvature with convex-cocompact fundamental group using results of Bunke and Olbrich. The method of proof forces us to exclude the spectral parameters corresponding to singular Poisson transforms.

Digitale Ressourcen im Psychologieunterricht - Brucks , Tabea; Buhl, Heike M. (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen. Ein Lehrbuch mit Unterrichtsmaterialien)

DART - Datengetriebene Methoden in der Regelungstechnik - Timmermann, Julia; Götte, Ricarda-Samantha; Junker, Annika; Hesse, Michael; Schwarzer, Luis
Im Zuge der Digitalisierung erfahren maschinelles Lernen und datengetriebene Methoden derzeit eine große Aufmerksamkeit in Wissenschaft und Industrie. Es fehlt jedoch an Grundlagenwissen und Verständnis, wie die datengetriebenen Methoden der Informatik mit bewährten modellbasierten Ingenieursmethoden wie dem modellbasierten Entwurf in der Mechatronik und Methoden der Regelungstechnik sinnvoll kombiniert werden können, um hybride Modelle zu erhalten. Diese ingenieurwissenschaftlichen Methoden basieren auf physikalischen Verhaltensmodellen, die eine besonders verdichtete und interpretierbare Darstellung von Wissen darstellen und insbesondere kausale Zusammenhänge beschreiben. Für spezifische regelungstechnische Anwendungen gibt es umfangreiches Vorwissen in Form von bekannten Strukturen und Informationen, wie z.B. (Teil-)Modelle oder Parametersätze, die auch bei der Anwendung von Methoden wie dem maschinellen Lernen genutzt werden sollten. Eine solche sinnvolle systematische Verknüpfung ist wissenschaftlich, insbesondere im Hinblick auf die industrielle Anwendung, noch nicht ausreichend untersucht worden und sehr vielversprechend. In diesem Beitrag werden die Ergebnisse der Nachwuchsforschungsgruppe DART – Datengetriebene Methoden in der Regelungstechnik vorgestellt. Das Hauptziel war es, die synergetische Kombination von modell- und datengetriebenen Methoden für regelungstechnische Aufgaben zu erforschen und es werden alle wichtigen Forschungsergebnisse aber auch die verwendeten Grundprinzipien des maschinellen Lernens in diesem Beitrag dargestellt.

Blockchain‑based reputation systemsfor business‑to‑business services: designing a reputation mechanism to reduce information asymmetry in professional consulting - Hemmrich, Simon; Nissen, Volker; Beverungen, Daniel; Pauls, Josias Daniel Miño (Information Systems and e-Business Management)
Reputation systems to rate companies’ performances remain largely unexplored inresearch and are scarcely used in business-to-business (B2B) practice. Such systemsare essential for businesses seeking trustworthy partners, as they help reduce infor-mation asymmetry, lower buyers’ transaction risks, and allow high-quality serviceproviders to justify premium pricing. Unlike traditional review-based systems in thebusiness-to-consumer (B2C) context, we propose a B2B reputation mechanism inwhich buyers commit to a rating payment before a transaction. Once the buyer final-izes the rating, this payment is executed and recorded on a blockchain as an immu-table, secure ledger. Our system mimics natural trust-building mechanisms with rat-ings that are (1) monetary-based, (2) stake-based, (3) non-aggregated, (4) involvecounter-ratings, (5) selectively sellable, (6) individually comparable, (7) stored ona blockchain, (8) and monitored by a third instance. This system provides a novelapproach to fostering trust in B2B transactions by reducing information asymme-try and transaction risk. We illustrate the mechanism’s application in the consultingsector. Our analysis has identified 23 institutional trust and distrust dimensions thatpromote establishing institutional trust through the proposed mechanism. Qualita-tive interviews suggest that, while complex and challenging to apply, this mecha-nism can foster trust in B2B transactions. Given the low maturity in the applicationdomain—rating professional business services with business reputation systems—and solution domain—using monetary stakes for ratings, this system stands as apotential invention.
Keywords: Information asymmetry; Trust; Reputation system; Monetary rating; Blockchain; Consulting

A Design Theory for Blockchain-Based Reputation Systems : Trust and Coordination in B2B Markets - Hemmrich, Simon
Keywords: Reputation Systems; Rating systems; monetary ratings; incentive mechanism; systems theory; Market coordination; advanced review system

Innovative lead-free ultrasonic bending transducers for low to medium power applications - Bornmann, Peter; Littmann, Walter; Scheidemann, Claus; Hemsel, Tobias
Nowadays ultrasound technology is established in various fields of application like industrial production or medical technology. Besides high power ultrasound applications like ultrasonic cleaning and ultrasonic welding, which are often not strongly restricted regarding their weight, costs, and construction space, there are many applications in the low to medium power range like handheld surgical instruments, medical inhalers, or ultrasonic cutters. For the latter there is often a strong demand for low weight and construction space and low costs to be competitive in mass production. Another challenge that arises from the RoHS-directive [1] is, that new ultrasonic devices should avoid the use of lead-containing PZT-materials. Against this background there is a demand for lead-free, small and lightweight and cost-effective ultrasonic transducers. In many of the above-mentioned applications, pre-stressed Bolted-Langevine-Transducers (BLT) based on lead-containing PZT-materials are established to generate ultrasonic vibrations. These are quite advantageous in many ways and can be built tailored to each application and even for high power of thousands of watts. But due to the required steps during their manufacturing process (machining parts, assembly, pre-stressing, frequency tuning, …), these transducers remain expensive. Furthermore, due to the operation in resonance, the construction space of these transducers is linked to their wavelength and cannot be reduced remarkably. For these reasons, our aim is to present an innovative lead-free ultrasonic transducer for low to medium power applications, that is based on bending vibrations instead of longitudinal vibrations. This design enables to build very small transducers. Furthermore, due to their simple construction, these transducers can be built at low manufacturing costs and are well suited for industrial mass production. The use of lead-free piezoelectric materials makes this transducer design ready for future applications. In our contribution we will present the model-based design of a lead-free 30 kHz bending transducer for applications up to 10 W. Furthermore, the comprehensive experimental analysis of this transducer-prototype in applications like mist generation or ultrasonic drilling will be presented. The results will be compared to a PZT-based bending transducer and a classical BLT to show the potential and limits of these kind of transducers and lead-free materials.

Power ultrasonic actuators with suddenly changing loads: How to control the amplitudes in resonance, antiresonance, or in-between - Littmann, Walter; Bornmann, Peter; Hemsel, Tobias; Scheidemann, Claus
Power ultrasonic actuators are used in various industrial, automotive and medical applications. Examples are ultrasonic welding of plastics or metal, surgery processes like cutting of tissue or bone, and the excitation of cavitation in liquids for ultrasonic cleaning. From a physical point of view, many of these processes are characterised by non-constant damping conditions for the ultrasonic actuators, since the systems need to be driven in unloaded as well as in high-loaded states. To get high power output, the piezoelectric actuators are usually driven in or near resonance at precisely defined vibration amplitudes. This is a quite complicated task especially if cost or mass optimized PZT transducers are used or if lead-free piezoelectric ceramics are applied to replace lead-containing materials. In particular the sudden change between loading states is very challenging for electronic excitation and control. The present contribution gives insight into typical problems that may arise in context with sudden load-changes during operation, e.g. uncontrolled jumps in voltage and velocity amplitudes. Measurements on ultrasonic power actuators being abruptly immersed into water at high amplitude are discussed for illustration. Observations during spontaneous load-changes are explained, and it is shown that several problems may be defused by driving the actuators in antiresonance or using a particular driving point in-between resonance and antiresonance (“falling edge control”). The different control strategies are investigated always using just one single hardware.

(mit K. Ruffing) Von Gerste, Göttern, Geld und Gesetzen. Eine Kultur- und Wirtschaftsgeschichte von Bier in der Antike

Semiramis - Droß-Krüpe, Kerstin (The Oxford Classical Dictionary)

Sardanapalus - Droß-Krüpe, Kerstin (The Oxford Classical Dictionary)

Frauenbilder und -rollen - Droß-Krüpe, Kerstin (Das achaimenidisch-persische Imperium)

Frauen als Gewalttäterinnen? Erste Überlegungen auf Basis von Petitionen aus dem griechisch-römischen Ägypten - Droß-Krüpe, Kerstin (Kriegerinnen im Altertum)

Atossa - Droß-Krüpe, Kerstin (Das achaimenidisch-persische Imperium)

What is Digital Fascism? - Fuchs, Christian (St. Anthony’s International Review)

Pasados presentes. La construcción de estereotipos de género en la recepción del mundo antiguo (Arenal. Revista de historia de las mujeres)

Sexuelle Bildung und (außer-)schulische Bildungspartner - Diederich, Julia; Magdeburg, Lena Maria (Sexuelle Bildung in der Grundschule und der universitären Lehrer*innenausbildung. Perspektiven aus Forschung, Praxis und Lehre)